1997
DOI: 10.1099/00221287-143-9-2991
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Aspergillus niger creA mutants and effects of the mutations on expression of arabinases and L-arabinose catabolic enzymes

Abstract: Aspergillus niger mutants relieved of carbon repression were isolated from an areA parental strain by selection of colonies that exhibited improved growth on a combination of 4-aminobutanoic acid (GABA) and D-glucose. In addition to derepression of the utilization of GABA as a nitrogen source in the presence of D-glucose, three of the four mutants also showed derepression of Lalanine and L-proline utilization. Transformation of the mutants with the A. niger creA gene, encoding the repressor protein CREA, re-es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 36 publications
3
42
0
Order By: Relevance
“…This protein is likely to be the A. nidulans equivalent of AxhA from A. tubingensis. AxhA was found to release Larabinose residues from ara binoxylans only (Kormelink et al, 1991), and its expression was induced by Larabitol (Gielkens et al, 1997). The A. tubingensis…”
Section: Regulation Of Abfb Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein is likely to be the A. nidulans equivalent of AxhA from A. tubingensis. AxhA was found to release Larabinose residues from ara binoxylans only (Kormelink et al, 1991), and its expression was induced by Larabitol (Gielkens et al, 1997). The A. tubingensis…”
Section: Regulation Of Abfb Expressionmentioning
confidence: 99%
“…In A. niger, the synthesis of these enzymes is induced by both L-arabinose, the final product of L-arabinan degradation, and by L-arabitol, an intermediate in the catabolic pathway of L-arabinose, though the latter is a stronger inducer ( Van der Veen et al, 1993). Furthermore, the expression of the L-arabinanase system is under carbon-catabolite repression when more preferable carbon sources like D-glucose are present in the medium Ruijter et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…While this result suggests a role of CreA in controlling the expression of rhtA and rhaB, as reported before for other sugar utilisation systems (Ademark et al, 2001;de Vries et al, 1999;Niu et al, 2015;Ruijter et al, 1997a), a different glucose-repression mechanism seems to have a major role in the transcriptional regulation of these genes. The existence of CreA-independent glucose repression mechanisms controlling the regulation of α-L-rhamnosidase genes (Tamayo- Ramos et al, 2012), and the phenylacetic acid uptake system (Cubero et al, 2000), has been previously reported in A. nidulans.…”
Section: Discussionmentioning
confidence: 42%
“…This complements the pyrA6 transformation marker and restores the uridine prototrophy. In addition, we measured citrate production under low iron stress (no iron added to the medium, see Supplementary file 1) in A. niger NW129 (cspA1, goxC17, pyrA1) (Ruijter et al, 1997a).…”
Section: Strains Media and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation